2021
DOI: 10.1155/2021/9954615
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Applications in Orthodontics: Changing the Face of Contemporary Clinical Care

Abstract: The last decade (2010-2021) has witnessed the evolution of robotic applications in orthodontics. This review scopes and analyzes published orthodontic literature in eight different domains: (1) robotic dental assistants; (2) robotics in diagnosis and simulation of orthodontic problems; (3) robotics in orthodontic patient education, teaching, and training; (4) wire bending and customized appliance robotics; (5) nanorobots/microrobots for acceleration of tooth movement and for remote monitoring; (6) robotics in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 131 publications
(153 reference statements)
0
17
0
Order By: Relevance
“…Modern technologies could aid to improve cantilever design and improve the treatment flow. In the last decade, the interest in the field of robotic wire bending and robotic customization of CAD/CAM appliances has increased [ 64 ]. To improve the precision, cantilevers could be designed in the software and bend indirectly by the robots.…”
Section: Discussionmentioning
confidence: 99%
“…Modern technologies could aid to improve cantilever design and improve the treatment flow. In the last decade, the interest in the field of robotic wire bending and robotic customization of CAD/CAM appliances has increased [ 64 ]. To improve the precision, cantilevers could be designed in the software and bend indirectly by the robots.…”
Section: Discussionmentioning
confidence: 99%
“…In 2017, Yuan et al demonstrated that robots' tooth preparation skills, such as laminate veneer and crowns preparations, are as accurate as those of human dentists [76]. Recently, a mobile wire-bending machine was introduced, which is capable of creating a fixed orthodontic retainer wire by means of intraoral scan data in only four minutes [77]. Another remarkable opportunity enabled by robotics is computer-assisted surgery.…”
Section: Artificial Intelligence and Roboticsmentioning
confidence: 99%
“…The guidance to the dentist is realized by the device position projecting onto the digital image of the anatomic area of interest, providing help in real-time to follow the anticipated pathways and allowing the doctor to recognize possible interference with the neighbouring tissues. Currently, the most commonly used optical tracking systems are based on capturing the position of a series of light-emitting diodes mounted on a surgical device [77]. In the future, virtual robotic surgery will allow surgeons to operate patients in a different location.…”
Section: Artificial Intelligence and Roboticsmentioning
confidence: 99%
“…[18] Our team has extensive knowledge and research experience that has translated into high quality publications. [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31]- [35] [36], [37], [38] This study aims at finding the prevalence of spacing in a specific South Indian population.…”
Section: Introductionmentioning
confidence: 99%